PRESUPPOSITION USED IN VOICE OVER OF TANGKIS PROGRAM ON INEWS TV MEDAN - Amirul Mukmin Nasution; Elia Masa Gintings (State University of Medan, 2015)
This research focused on presupposition used in Voice Over of Tangkis programon Deli TV (now iNews TV). This research conducted by using descriptivequalitative in which the writer describes and analyze the meaning of the script of anews. The data were taken from voice over of Tangkis program on Deli TV. Thefindings shown that there were 305 utterances contained five from six types ofpresupposition. The result of this research show that voice over of Tangkisprogram on Deli TV tends to use Existential Presupposition (72%), FactivePresupposition (5%), Lexical Presupposition (6%), Non-Factive Presupposition(12%), and Counterfactual Presupposition (5%). The dominant type is ExistentialPresupposition, which means that the voice over purposed to tell the reader a newsthat happening to somebody especially crime such as murder and accident.